Nickel nanoparticles: a novel platform for cancer-targeted delivery and multimodal therapy - Wang, Fengyu; Tong, Sen; Ma, Xuan; Yang, Huan; Zhang, Tianbao; Wu, Kunrong; Wu, Junzi (Frontiers in Drug Delivery, 2025)
Traditional cancer treatment methods often encounter limitations, such as poor targeting, low bioavailability, and high systemic toxicity. These challenges have led researchers to explore alternative therapeutic strategies. Nickel nanoparticles (NiNPs), owing to their distinctive physicochemical properties and tunable biocompatibility, have attracted considerable attention in cancer therapy and drug delivery applications. These nanomaterials demonstrate excellent magnetic properties, photothermal conversion capabilities, catalytic activity, and potential for multifunctionality and targeted drug delivery via surface modification. This review highlights recent advancements in the use of NiNPs for cancer treatment, emphasizing their advantages as drug carriers that enhance the bioavailability, targeting, and therapeutic efficacy of anticancer agents. Additionally, the synergistic applications of NiNPs in multimodal therapies, including magnetic hyperthermia, photothermal therapy, and chemodynamic therapy, are discussed, as well as their potential as theranostic platforms. Although nickel-based nanodelivery systems show significant promise for clinical translation, issues related to biosafety, degradation metabolism, and long-term toxicity remain and require further investigation to support their clinical application.